2018
DOI: 10.3382/ps/pey222
|View full text |Cite
|
Sign up to set email alerts
|

What drives the choice of poultry market channel and the change of purchase behavior due to highly pathogenic avian influenza outbreaks?

Abstract: In Indonesia, market channels play an important role in food security in poultry meats. This review explains Indonesian consumers' choice of market channels to purchase poultry, and consumer concern of food scares and food safety in their consumption due to highly pathology avian influenza (HPAI) outbreak. The survey was conducted for the traditional and the modern channels and involves a sample of 1096 respondents in the Greater Jakarta Area. The logistic regression analysis reports the model proved that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 23 publications
2
23
0
Order By: Relevance
“…Then the variables will be used to analyze each characteristic effect in the logistic regression model of the channel choice and purchase behavior. Similar approach was used in different animal disease study by Indrawan, et al [10].…”
Section: The Choice Of Dog Trade Channelmentioning
confidence: 99%
“…Then the variables will be used to analyze each characteristic effect in the logistic regression model of the channel choice and purchase behavior. Similar approach was used in different animal disease study by Indrawan, et al [10].…”
Section: The Choice Of Dog Trade Channelmentioning
confidence: 99%
“…On the other hand, animal diseases cause major economic loss through and less efficient production shown by mortality, reduced productivity, lower fertility, condemned products, and restricted access to potential markets. Furthermore, many consumers consume less healthy animal products [10,11]. As a result, less productive farm impacts their ability to recover quickly.…”
Section: The Recession and Long-run Effect On Health: The One Heamentioning
confidence: 99%
“…In the context of the Indonesian poultry meat sector, freshness can be defined in three levels: warm, chilled, and frozen (Daryanto et al, 2014;Indrawan et al, 2018a). A previous study showed that in Indonesia freshness is defined differently than in western countries (Indrawan et al, 2018b), since many of the consumers prefer to buy poultry meat in the traditional channel, where the food safety level is lower than in the modern channel (Muladno and Thieme, 2009).…”
Section: Selection Of Poultry Meat Attributes and Consumers' Wtpmentioning
confidence: 99%
“…The Indonesia poultry meat industry faced a food safety challenge after the outbreak of highly pathogenic avian influenza (HPAI) H5N1 in 2005 because of a complex poultry chain structure with an interaction between traditional and modern channels where a sick poultry market exist (Indrawan et al, 2018a). Three factors can be identified as the main sources of the food safety challenge: first, the current food safety control systems in Indonesia are weak (Bahri, 2008;Hariyadi, 2008); second, some consumers prefer to buy poultry meat from traditional channel with low food safety levels (Indrawan et al, 2018a;Indrawan et al, 2018b;Muladno and Thieme, 2009); third, some consumers were taken into account price and freshness presentation when purchasing poultry (Daryanto et al, 2014;Indrawan et al, 2018a;Indrawan et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation